2002
DOI: 10.1653/0015-4040(2002)085[0588:danpos]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Natural Parasitism of Spodoptera Frugiperda (Lepidoptera: Noctuidae) Eggs at Different Phenological Stages of Corn

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 10 publications
2
23
0
3
Order By: Relevance
“…It is important to consider that not only S. cosmioides, but also other species of the Spodoptera complex have increased their importance on crops such as soybean, corn and cotton. Another noticeable issue is that T. remus can effectively parasitize the inner layers of the egg masses (Cruz & Figueiredo 1994), whereas the parasitoids from the Trichogramma genus are able to parasitize only the outer layers (Beserra et al 2002). Therefore, T. remus can be considered as an efficient biocontrol agent of S. frugiperda eggs (Johnson 1984), as well as of the other species of Spodoptera that lay eggs in layered clusters, such as S. cosmioides.…”
Section: Resultsmentioning
confidence: 99%
“…It is important to consider that not only S. cosmioides, but also other species of the Spodoptera complex have increased their importance on crops such as soybean, corn and cotton. Another noticeable issue is that T. remus can effectively parasitize the inner layers of the egg masses (Cruz & Figueiredo 1994), whereas the parasitoids from the Trichogramma genus are able to parasitize only the outer layers (Beserra et al 2002). Therefore, T. remus can be considered as an efficient biocontrol agent of S. frugiperda eggs (Johnson 1984), as well as of the other species of Spodoptera that lay eggs in layered clusters, such as S. cosmioides.…”
Section: Resultsmentioning
confidence: 99%
“…There have been surveys for natural enemies of fall armyworm in the USA (Hogg et al 1982;Ashley 1986;Meagher et al 2016), Mexico and Central America (Castro & Pitre 1989;Molina-Ochoa et al 2003), and South America (Beserra et al 2002;Murúa et al 2009). Although some species exist throughout the Western Hemisphere, most species' distribution generally is defined by their geographic areas (Ashley 1979).…”
Section: Palabras Claves: Control Biológico; Cotesia Bifoveolatus; Phmentioning
confidence: 99%
“…The presence of Trichogramma atopovirilia Oatman & Platner, 1983 parasitizing eggs of that pest in corn crops demonstrates the potential of use of this parasitoid for the control of S. frugiperda (Zucchi et al, 1991;Alvarez & Roa, 1995;Zucchi & Monteiro, 1997;Beserra et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been observed that S. frugiperda egg masses parasitized by Trichogramma under field conditions are rare (Rueda & Victoria, 1993); some authors have questioned its use as a control agent, due to the fact that the eggs of the pest are arranged in superimposed layers, and to the presence of scales that make the parasitoid action harder (Toonders & Sánchez, 1987;Sifontes et al, 1988;Armas & Ayala, 1993;Beserra et al, 2002). Beserra et al (2002) observed a low parasitism (2.21%) of S. frugiperda eggs in corn; the species Trichogramma pretiosum Riley, 1879 was the most abundant and occurred in 93.79% of the samples, while T. atopovirilia only represented 2.07%. Even in young rice plants, where egg masses are relatively small, parasitism by Trichogramma is difficult, since only 20 to 40% of the eggs are accessible for parasitism (Sifontes et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation